Saving-Investment Nexus in Developing Countries: Does Financial Development Matter? (2013)
The Feldstein-Horioka puzzle is re-examined using a sample of 20 sub-Saharan Africa (SSA) countries. Unlike the extant literature we demonstrate the expediency of sustenance of financial sector reforms for the saving-investment nexus in SSA. Findings showed saving retention coefficients similar in magnitude to those already reported for developing countries, particularly SSA. In addition, however, the results uncovered a telling intervening role for financial deepening in the saving-investment space. Going forward, the precise nature and corresponding policy implications of this role should form an integral part of discussions in both academic and policy circles.